2016
DOI: 10.1007/s00281-016-0577-x
|View full text |Cite
|
Sign up to set email alerts
|

A new era in reproductive medicine: consequences of third-party oocyte donation for maternal and fetal health

Abstract: The fetus is a semi-allograft for the maternal host in natural pregnancy, but the fetus is a complete allograft after oocyte donation (OD), and there is greater antigenic dissimilarity with the mother. Thus, OD pregnancy is a good model for understanding how the fetus is protected by the maternal immune system. Recent clinical data have revealed a higher risk of miscarriage, gestational hypertension, preterm birth, and low birth weight with OD pregnancy. There is also a higher incidence of chorionic deciduitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 83 publications
(116 reference statements)
0
22
1
1
Order By: Relevance
“…Severe maternal morbidity may not only herald maternal mortality but is also associated with significant healthcare cost, long‐lasting rehabilitation programmes, and family burden. Based on recent trends in high‐income countries, the annual rate of women experiencing severe maternal morbidity has been steadily rising . Increases in severe maternal morbidity are believed to result from a combination of factors, including advanced maternal age, prepregnancy obesity, pre‐existing chronic conditions, and caesarean delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe maternal morbidity may not only herald maternal mortality but is also associated with significant healthcare cost, long‐lasting rehabilitation programmes, and family burden. Based on recent trends in high‐income countries, the annual rate of women experiencing severe maternal morbidity has been steadily rising . Increases in severe maternal morbidity are believed to result from a combination of factors, including advanced maternal age, prepregnancy obesity, pre‐existing chronic conditions, and caesarean delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Based on recent trends in high-income countries, the annual rate of women experiencing severe maternal morbidity has been steadily rising. 25,26 Increases in severe maternal morbidity are believed to result from a combination of factors, including advanced maternal age, prepregnancy obesity, pre-existing chronic conditions, and caesarean delivery. The results of this study suggest that the increasing use of ART might be one of the determinants of the observed increase in maternal morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Una reciente revisión sistemática y metanálisis reportó que los embarazos obtenidos por DO presentan un riesgo mayor de SHE (OR 2.63, IC 95% 2.17-3.18), preeclampsia (OR 2.64, IC 95% 2.29-3.04), preeclampsia severa (OR 3.22, IC 95% 2.30-4.49), PP (OR 1.57, IC 95% 1.33-1.86) y BPN (OR 1.25, IC 95% 1.20-1.30) comparado con los embarazos obtenidos por FIV autóloga 45 . El mayor riesgo de trastornos hipertensivos podría estar asociado a factores como la edad materna avanzada y una mayor prevalencia de patologías médicas, a la vez que a defectos en la placentación inducidos por la preparación endometrial artificial y una eventual incompatibilidad inmunológica a antígenos derivados del feto 46 .…”
Section: Tra Especiales De Alta Complejidad Donación De Ovocitosunclassified
“…In an oocyte donation pregnancy, the fetus is fully allogeneic towards the mother, since it carries both oocyte donor antigens and paternal antigens; this antigenic dissimilarity in unmatched oocyte donation pregnancies is comparable to the antigenic dissimilarity in unmatched organ transplantation [5]. Due to the enhanced allogeneic nature of oocyte donation, these pregnancies presumably need more or different maternal immune adaptations, compared to naturally conceived pregnancies [5,13,14,15]. The increased adaptive load on the immune system between naturally conceived and oocyte donation pregnancies may explain why the latter are more often accompanied by immune-disturbance related obstetrical complications, such as pregnancy induced hypertension and pre-eclampsia [13,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the enhanced allogeneic nature of oocyte donation, these pregnancies presumably need more or different maternal immune adaptations, compared to naturally conceived pregnancies [5,13,14,15]. The increased adaptive load on the immune system between naturally conceived and oocyte donation pregnancies may explain why the latter are more often accompanied by immune-disturbance related obstetrical complications, such as pregnancy induced hypertension and pre-eclampsia [13,15,16]. Oocyte donation pregnancies more often coincide with other risk factors for pregnancy complications, such as the self-evident need for artificial reproductive techniques, advanced maternal age, primiparity, cause of infertility, and multiple gestations [17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%